Human NOC3 is essential for DNA replication licensing in human cells. Issue 5 (4th March 2019) - Cheung, Man-Hei; Amin, Aftab; Wu, Rentian; Qin, Yan; Zou, Lan; Yu, Zhiling; Liang, Chun
ABSTRACT: Noc3p (Nucleolar Complex-associated protein) is an essential protein in budding yeast DNA replication licensing. Noc3p mediates the loading of Cdc6p and MCM proteins onto replication origins during the M-to-G1 transition by interacting with ORC (Origin Recognition Complex) and MCM (Minichromosome Maintenance) proteins. FAD24 (Factor for Adipocyte Differentiation, clone number 24), the human homolog of Noc3p (hNOC3), was previously reported to play roles in the regulation of DNA replication and proliferation in human cells. However, the role of hNOC3 in replication licensing was unclear. Here we report that hNOC3 physically interacts with multiple human pre-replicative complex (pre-RC) proteins and associates with known replication origins throughout the cell cycle. Moreover, knockdown of hNOC3 in HeLa cells abrogates the chromatin association of other pre-RC proteins including hCDC6 and hMCM, leading to DNA replication defects and eventual apoptosis in an abortive S-phase. In comparison, specific inhibition of the ribosome biogenesis pathway by preventing pre-rRNA synthesis, does not lead to any cell cycle or DNA replication defect or apoptosis in the same timeframe as the hNOC3 knockdown experiments. Our findings strongly suggest that hNOC3 plays an essential role in pre-RC formation and the initiation of DNA replication independent of its potential role in ribosome biogenesis in human cells.